Superposition of free and bound exciton emission spectra in ZnP2-D48 - Stamov, Ivan (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
Bound exciton lines are found in the luminescence spectra of Mn, Sn, Cd, and Sb doped tetragonal zinc diphosphide crystals at the temperature of 10 K. Zero phonon lines of bound and free exciton emission, as well as their phonon replica, are identified in the spectra. The emission lines are described in terms of levels of an axial center. The superposition of luminescence due to free excitons and excitons bound to the axial center is investigated in detail. The amplification of lines associated with forbidden transitions of bound excitons is observed in the region of phonon replica of free exciton recombination.